Genomic variance partitioning of carcass and meat quality traits in Angus beef cattle - Baneh, Hasan; Elatkin, Nikolay; Gentzbittel, Laurent (Frontiers in Veterinary Science, 2025)
This study aimed to partition the genomic variance of carcass weight (CW), marbling score (MS), rib-eye area (REA), and back fat thickness (BFT) traits in Angus beef cattle into components associated with minor allele frequency (MAF) bins, functional annotation classes, and chromosomes. The dataset included 6,511,978 (6.5 million) imputed whole-genome sequence (WGS) SNPs from 13,241 Angus beef cattle. Genomic partitioning was performed using a multi-component mixed linear model analysis, modeling random effects with multiple genomic relationship matrices (GRMs), either simultaneously (joint analysis) or separately (separate analysis). The estimated heritability (h2) for CW, MS, REA, and BFT, obtained by fitting all 6.5 million SNPs at once, was 0.22 ± 0.01, 0.25 ± 0.01, 0.35 ± 0.01, and 0.15 ± 0.01, respectively. The aggregate genetic variance components estimated from the separate analysis were substantially larger than the corresponding heritability estimates, while the results of joint analysis for all partitioning factor were very close to h2 estimates for all traits. A weak relationship was observed between chromosome length and its heritability (R2 < 0.35). Although intergenic and intronic variants significantly contributed to the genetic variation of the traits, the variance captured per SNP was considerably lower for these variants compared to genic variants, particularly exon variants.